THE EFFECT OF MANGGROVE FRUIT ORGANIC FERTILIZER CONCENTRATION (Abelmoschusesculentus L. Moench) OKRA CULTIVATION - pria nugraha hasibuan; dwi zulfita; surachman surachman (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT               This study aims to increase the pH of peat soil by giving mangrove fruit POC on peat soil. This research starts from May 31 to August 24 2018, The research was carried out in the great road VII block Y. The method used in the Completely Randomized Design consisted of 5 treatments, 5 replications and each replication there were 4 plant samples. The treatment was as follows: (P1) 5 ml / water, (p2) 10 ml / water, (p3) 15 ml / water, (p4) 20 ml / water and (p5) 25 ml / water. The variables observed in this study were root volume (cm3), Total Leaf Area (cm2) dry weight (g), leaf chlorophyll (sped unit), plant height (cm), number of fresh fruit (g) and weight of planting fruit (g ). The results showed that the administration of mangrove POC with a concentration of 15ml / liter of water showed the best growth and yield of okra on peat soil. Keywords:POC, peat soil, okra